The relationship between psychological capital, stress, micro-learning environment, and professional identity in nursing interns: a structural equation modeling study - Gong, Boxiong; Chen, Xin; Wang, Na; Zhan, Yan; Zhong, Huiqin; Zhang, Rong; Luo, Yi; Zhang, Zhentong; Li, Longti (Frontiers in Psychology, 2025)
BackgroundNursing interns play a crucial role in shaping the future nursing workforce, as their professional identity is closely linked to workplace retention rates and patient outcomes. Thus, investigating the factors that influence nursing interns' professional identity is important.ObjectiveTo evaluate the relationship between psychological capital, stress, micro-learning environment, and professional identity among nursing interns.MethodsThis was a cross-sectional study. The sample consisted of 388 nursing interns from 8 comprehensive teaching hospitals across five cities in Hubei Province between March and April 2024. Data were collected using a Descriptive Information Questionnaire, the Psychological Capital Questionnaire, the Student Nurse Stress Index scale, the Healthcare Education Micro Learning Environment Measure, and the Professional Identity Scale. The structural equation model was applied to explore the influencing factors of nursing interns' professional identity.ResultsThe mean total score for professional identity was 35.57 ± 7.47. Psychological capital positively influenced professional identity directly (β = 0.16, P < 0.01), while stress as measured using the student nurse stress index had a negative impact (β = −0.20, P < 0.01). High scores on the healthcare education micro-learning environment measure positively contributed to the development of professional identity (β = 0.69, P < 0.001). Furthermore, psychological capital was identified as a mediator in the association between the healthcare education micro learning environment and professional identity, as well as between the student nurse stress index scores and professional identity.ConclusionThe study suggests that a higher level of psychological capital, low stress levels, and a satisfied micro-learning environment are essential in fostering professional identity among nursing interns. It recommends collaboration between nursing schools and clinical departments to enhance nursing interns' psychological capital and stress management skills, creating a positive and safe working environment, thereby fostering professional identity among nursing interns.